Sea + Survival: choreographing dune systems to defend against sea-level rise - Sendall, Abigail Victoria (School of Architecture, Planning and Geomatics, 2021)
Sea-level rise is on the forefront of global climate change concerns with an estimated 800 million people at risk of experiencing the devastating social, economic, and environmental impacts of rising seas and storm surges (C40 Cities, n.d.). In particular, coastal towns and cities are under immense pressure as major solutions are needed to ensure the resilience of these spaces. Langebaan, in the Greater Saldanha Region along the Western Cape, South Africa is suffering from the effects of poorly planned linear coastal development that has suffocated the protective dune systems and public beach space. Where, according to the Sea Level Rise and Flood Risk Assessment for a Select Disaster-Prone Area Along the Western Cape Coast Report, Langebaan is specifically mentioned for being highly susceptible to coastal erosion and storm swell damage (Blake & Chimboza, 2011). The town is a fast-growing holiday destination and retirement area, which has led many of the new developments to be privatised, commandeering large portions of the coastal beachfront. The small portion of the beach that is then left for the local communities to enjoy is the most at risk to sea-level rise. It is at this moment where my dissertation lands itself, in the investigation of the pinch-point between human and nature; the human treatment of the coastal 'dunescape', and the ecosystem services of coastal dunes amid a climate crisis. Due to the constrained nature of the coast, sea defences are required to take place offshore, therefore, I propose a land claim in the form of an ecological island. This thesis harnesses the existing ecological systems in and around the area to form a buffer between Langebaan and the sea. The defence system acts to unsuffocate dunes and public space in Langebaan by claiming land for ecological systems and humans. Overall, this thesis illustrates the importance of the envelopment of the human and the natural in reacting to climate change and creates an accessible, sensitive, and meaningful space, revealing the memory of the site.